Jalan Panjang Menuju Pengesahan APBD: Berdasarkan Sudut Pandang Agency Theory - Achmad Helmi Hasan; Bambang Haryadi; Yuni Rimawati (Jurnal Keuangan dan Perbankan, 2015)
Process pre-prosperous the preparation, the preparation, discussion and ratification of the budget should be based on the applicable legislation (Permendagri No. 13/2006 junto Permendagri No.59/2008). Phenomenon that occurs, still many local government that overdue their budget, although there are sanctions should that happen. This research aims to provide a more comprehensive explanation of the executive and legislative relationship in Local Government X is reviewed from the perspective of agency theory to ratification of local government annual budget. This study uses qualitative methods a descriptive case study.Based on the results of this research was concluded that (1) The lateness of the budget local governmet X is because of delays of drafting the support documents that is required in the budget by the executive, thus causing delays of filing budget to the legislature; (2) viewed from the side agent (the sectoral egos of executive) mean while, from the principle/legislative (interest group / political party and a constituent) also coloring the process.